223k views
1 vote
F(x)=2(x-4)(x+1) how do i convert this factored form to standard form?

User Mdarwin
by
5.6k points

1 Answer

1 vote

I'd would do the FOIL method and then distribute the 2. But you can also distribute first. Either way, they want you to expand it.

(x - 4)(x + 1) = x(x) + x(1) - 4(x) - 4(1)

Simplify

x² + 1x - 4x - 4

Combine like terms:

x² - 3x - 4

Now, bring back that 2 to distribute.

2(x² - 3x - 4) = 2(x²) + 2(- 3x) + 2(- 4)

f(x) = 2x² - 6x - 8

User Derek Greer
by
5.6k points